Color-conscious paradigms of adult and educational leadership development through culturally relevant mentoring: Africentricity, and critical spirituality explored. - Phillip A Smith (Adult Education Research Conference, 2016)
This conceptual paper draws on the indigenous wisdoms of the African Diaspora, and critical spirituality. It strives to formulate a new definition of culturally relevant mentoring for educational leadership development as applicable to the leadership development of Black male secondary school principals and other senior educational leaders.
Keywords: culturally relevant mentoring; Africentric adult learning; critical spirituality; educational leadership development